Impact of large-scale renewable power plants on the tie-line loadings of a Vietnamese power network - Bao, Doan Thanh; Ninh, Nguyen Van; Lam, Nguyen Van; Le, Tuan-Ho (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The rapid integration of wind power and power solar plants into the electrical power system has caused several operation issues in recent decades. To investigate the impact of large-scale renewable power plants on the tie-line loadings of a practical power grid, the 110 kV power network of Binh Dinh province, Vietnam is utilized in this paper. This power network with and without three solar power plants (including Fujiwara plant with a peak capacity of 50 MWp, Cat Hiep plant with a peak capacity of 49.5 MWp, and Dam Tra O plant with a peak capacity of 50 MWp) and three wind power plants (including Nhon Hoi plant with a capacity of 60MW, Phuong Mai 1 plant with a capacity of 26.4 MW, and Phuong Mai 3 plant with a capacity of 20.7 MW) is modeled by using the PSS/E software to examine the tie-line loadings capacity. The simulation results showed that the tie-line loadings of the current power network increase when six renewable power plants are integrated into this network. Therefore, three different scenarios to upgrade the existing power network are proposed. The final results demonstrated the efficiency of the proposed scenarios in solving the tie-line loadings issue of the practical power network.